3D parameter to quantify the anisotropy measurement of periodic structures on rough surfaces. Issue 1 (3rd July 2013) - Guillemot, G.; Bigerelle, M.; Khawaja, Z.; Brown, Christopher A.
Summary In this paper, a new 3D roughness parameter, Sreg, is proposed to quantify the regularity of a surface, independent of the amplitude and the SCANNING 36:127–133, 2014. © 2013 Wiley Periodicals, Inc.